Thienylpyrrole azo dyes: synthesis, solvatochromic and electrochemical properties - Raposo, M. Manuela M. (2005)
The synthesis and the evaluation of solvatochromic and electrochemical properties of new donor-acceptor-substituted thienylpyrrole azo dyes 3 are described. These derivatives exhibit dramatic changes in both their electronic and redox properties in comparison with thienylpyrroles 1. In agreement with the solvatochromic and electrochemical studies of push-pull derivatives 3 the new compounds prepared, may find application in the manufacture of new materials with notable non-linear optical properties.